The Gender Empowerment in Disney's Live Action Mulan (2020) : A Feminist Perspective - Putri, Rezza Almiana; M. Thoyibi (Universitas Cokroaminoto Palopo, 2024)
Gender empowerment is an effort to achieve equality and justice between women and men and eliminate inequality and discrimination based on sex. Disney’s Live Action Mulan (2020) is one of the movies with the theme of gender empowerment. The technique in this research uses a literature study. This research analyzes gender empowerment in Disney’s Live Action Mulan (2020). This research uses feminism theory with a focus on liberal feminism theory. The data sources used include primary data from the Disney’s Live Action Mulan (2020) and secondary data from previous research, such as theses, and related journals. There are three results found. There are five indicators of gender empowerment contained in Disney’s Live Action Mulan (2020). The second is the depiction of gender empowerment, and the last is the reason why researchers discuss gender empowerment.